Design of Cycle Detection System for Locomotive On-board Electric Service Equipment - WU Junliang; YANG Jiang (Kongzhi Yu Xinxi Jishu)
Aiming at enhancing equipment quality hazard monitoring level, improving production management efficiency and reducing the risk caused by human factors, the management situation of the detection and quality monitoring for locomotive on-board electric service equipment was researched based on LKJ equipment management system (LMD system). In this paper, it designed a cycle detection system used technologies of computer, wireless communication, satellite positioning, big data mining and processing analysis, which based on LMD for locomotive on-board electric service equipment, mainly including locomotive entry and exit judgment, quality analysis, file download and LKJ monitoring module. Users can keep abreast of the status of locomotive and on-board equipments, and detect operation information in time. Field application results show that the system can more efficiently realize cycle detection of locomotive on-board electric service equipment in a real-time and safe way than that of the traditional one.